Penyebab Sengketa Pengadaan Tanah untuk Kepentingan Umum (Studi Kasus Sengketa Pengadaan Tanah untuk Kepentingan Umum di Bengkulu) - Yanto Sufriadi (Jurnal Hukum IUS QUIA IUSTUM, 2011)
This research focuses on the causes of disputes use for land procurenment used for public importence occurring frequently in the past time how the position of traditional law in the legal substance of national land affairs is how the working procedures of the Land Procurenment Committee (legal structure) are, and how the legal culture of the internal land procurenment executor. This research uses the sociolegal approach and it also uses the data collected from the results of the field study and literature materials. This study concludes that the disputes in land procurenment used for public importance are caused by the centralis substance of the agrarian law, the legal structure of land procurenment executor regulated by the stric formal procedures, and the legal culture of the eecitive apparatus bound by the tradition of legal positivism throught.Key words : Land procurenment used for public importance, disputes, legal system